Botulinum Toxin Effects on Freezing of Gait in Parkinson’s Disease: A Systematic Review - Tambasco, Nicola; Nigro, Pasquale; Mechelli, Alessandro; Duranti, Michele; Parnetti, Lucilla (Toxins, 2024)
Freezing of gait is a frequent phenomenon and can be one of the most debilitating motor impairments in Parkinson’s disease, especially in the advanced stages. It is currently defined as a brief episodic absence or any marked reduction in the forward progression of the feet, despite the intention to walk. Greater severity of freezing of gait has been associated with more frequent falls, postural instability, and executive dysfunction. However, botulinum neurotoxin is one of the most widely administered therapies for motor and non-motor symptoms, including freezing of gait, in parkinsonism. To date, the literature has had conflicting results on the use of botulinum toxin in the treatment of freezing of gait in Parkinson’s disease patients. In light of this, we reviewed the findings of past studies that specifically investigated the effects of botulinum toxin on freezing of gait in Parkinson’s disease in order to better understand this issue.